INFORMATION SYSTEMS OF DENTAL RESERVATION MANAGEMENT ON DENTAL CLINIC - Nugraha, Ucu; Boga Kuswara, Galuh (International Journal of Psychosocial Rehabilitation, 2020)
Information systems are very helpful for management performance. Management information systems do not always use or need computer equipment in their operations, but in the era of rapid technological development now and demanded information can be presented quickly and accurately, the operational management really needs to be assisted with management information systems that use information technology devices. The iteration method is used as a method in developing this system, and the PIECES framework is used to categorize the problems that are found according to the needs of the community. The results of this study are in the form of a management information system that is able to manage clinical information quickly and precisely, as well as the information generated can be more accurate, and managers can more easily control the information system contained in the clinic.